2017
DOI: 10.1177/1559827617711906
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Status: Influence of Exercise and Diet Quality

Abstract: Physical activity, adherence to a healthy diet, and healthy beverage pattern are considered essential components of a healthy lifestyle. We aimed to evaluate the associations between physical exercise, diet quality, and total fluid intake, along with fluid recommendations compliance in a sample of adults. Data on fluid intake from different types of beverages were collected in a cross-sectional study, in 1161 men and women between 18 and 65 years of age, using a fluid-specific diary. Exercise was evaluated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Characteristics of the included studies are shown in Tables 1 and 2. Of the 105 included studies, 81 studies 20,23,25,26,28–30,32,34–46,48–56,58–65,67–71,74–76,78–84,86–92,95–99,101,103,104,106,109,113,115–124 were classified as studies primarily designed to measure fluid intake (intervention or observational studies), and 24 18,19,21,22,24,27,31,33,47,57,66,73,77,85,94,100,102,105,107,108,110–112,114 studies were classified as methodological studies evaluating accuracy and/or reliability of dietary assessment tools.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of the included studies are shown in Tables 1 and 2. Of the 105 included studies, 81 studies 20,23,25,26,28–30,32,34–46,48–56,58–65,67–71,74–76,78–84,86–92,95–99,101,103,104,106,109,113,115–124 were classified as studies primarily designed to measure fluid intake (intervention or observational studies), and 24 18,19,21,22,24,27,31,33,47,57,66,73,77,85,94,100,102,105,107,108,110–112,114 studies were classified as methodological studies evaluating accuracy and/or reliability of dietary assessment tools.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of the included studies are shown in Tables 1 and 2. Of the 105 included studies, 81 studies 20,23,25,26,[28][29][30]32,[34][35][36][37][38][39][40][41][42][43][44][45][46][48][49][50][51][52][53][54][55][56][58][59][60][61][62][63][64][65][67][68][69][70][71][74][75][76][78][79][80][81][82]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Pada penelitian ini, baik mahasiswa dan pegawai menunjukkan mayoritas memiliki tingkat aktivitas yang tinggi dan memiliki asupan cairan yang adekuat. Status hidrasi yang kurang/dehidrasi dapat mengurangi kemampuan fisiologis sistem tubuh, seperti kapasitas jantung paru, fisiologi muskuluskeletal, perhatian dan kemampuan kognitif (Fauza & Astuti, 2022;San Mauro Martín et al, 2019). Pada penelitian ini masih terdapat kondisi dehidrasi pada kedua kelompok.…”
Section: Gambar 1 Skala Status Hidrasi Berdasarkan Warna Urin (Urine ...unclassified
“…Pengetahuan yang akurat mengenai status hidrasi menjadi sangat penting didapatkan, terutama pada atlet. Status hidrasi pada atlet sangat mempengaruhi performance atlet dalam melakukan olahraga (Krabak, Lipman, Waite, & Rundell, 2017;San Mauro Martín et al, 2019).…”
Section: Gambar 1 Skala Status Hidrasi Berdasarkan Warna Urin (Urine ...unclassified